Response to comment on "rapid cooling and cold storage in a silicic magma reservoir recorded in individual crystals" - Cooper, Kari M. (2020)
In a recent paper, we used Li concentration profiles and U-Th ages to constrain the thermal conditions of magma storage. Wilson and co-authors argue that the data instead reflect control of Li behavior by charge balance during partitioning and not by experimentally determined diffusion rates. Their arguments are based on (i) a coupled diffusion mechanism for Li, which has been postulated but has not been documented to occur, and (ii) poorly constrained zircon growth rates combined with the assumption of continuous zircon crystallization.